Механізми затратного підходу до комплексної економічної оцінки природних ресурсів - Клиновий, Д.В. (Економіка природокористування і охорони довкілля, 2013)
Розглядаються місце, роль, завдання і механізми затратного підходу в комплексній економічній оцінці природних ресурсів в умовах ринку стосовно діяльності кластерно-корпоративних структур з управління природокористуванням. The place, role, tasks and mechanisms of the expensive approach in a complex economic assessment of natural resources in market conditions in the activity of cluster-corporate economic structures in natural resources management are considered in this article. Basic approaches to formation of expensive mechanisms of an expensive of natural resources in market conditions of managing on cluster-corporate basis with the use of financial and economic methods of a complex estimation of expenses in natural resources management are generated. The logistic mechanism of adaptation of expensive methods of natural resources economic assessment based on discount methods, the account of distribution of the cost of charges in time, the account of risks and all charges in the balanced circuit of the is natural resources management is offered.